Factors associated with specialty choice in Chinese medical students and residents: an exploratory cross-sectional study. Issue 1 (October 2019) - Kosik, Russell O; Fan, Lihong; Fan, Angela P; Zhao, Xudong; Hsu, Yunung; Lien, Selina S; Li, Dan; Lu, Christopher; Ren, Yuanpeng; Jiang, Baisheng; Chen, Qi
Abstract: Background: Specialty maldistribution stemming from a lack of preference for certain specialties can substantially impact a country's health-care system. Promoting primary care or addressing the shortages of certain specialties needs a better understanding of the underlying motives that might encourage or discourage medical students to choose certain specialties. We aimed to explore the predominant factors that influence specialty choice in China's medical students and physicians through a nationwide survey. Methods: From 2016 to 2017, an electronic survey was distributed to medical students and physicians across all seven administrative regions of China. We used validated instruments including the Job Contentment Questionnaire, the Professionalism Assessment Scale, the Chronic Fatigue Syndrome Symptom Inventory, the Maslach Burnout Inventory, the General Health Questionnaire (Chinese version), and a modified Center for Epidemiologic Studies Depression Scale. Ethical approval was obtained by the institutional review board of the principal investigator's institution. Findings: 2549 respondents from 85 medical schools and hospitals filled out the questionnaire. The most influential factors in determining specialty selection were quality of training (N=901 [35·3%], mean 3·8 [SD 1·1]), autonomy (876 [34·4%], 3·9 [1·1]), and social commitment (760 [29·8%], 3·7 [1·1]). By contrast, the least influential factors were salary, length of residency, and academic experience. Selection of quality of training and autonomy were positively associated with professional development and inversely associated with negative health outcomes. With the exception of salary, negative associations were found between all specialty choice factors (ie, comprehensibility, role models, family influence, specialty prestige, work–life balance, research opportunities, social commitment, variety of medical problems, and work style) and nearly all health burden variables. Interpretation: Focusing on ensuring autonomy in medical practice, enhancing the quality of training, and correcting outdated remuneration mechanisms might be the best way to ensure a proper balance of physicians across medical specialties. Funding: Republic of China Ministry of Science and Technology (MOST 105-2629-S-010-001).